IIUM Bachelor of Audiology tracer study - Abdul LAtif, Nordiana; Jamaluddin, Saiful Adli (Kulliyyah of Allied Health Sciences, IIUM, 2018)
This tracer was study designed to help the audiology education provider (AEP) at the International Islamic University Malaysia (IIUM) to trace alumni’s employment profile, their perception on academic and training program received in IIUM and to gather suggestions for further improvement on learning and teaching activities. Insights received will enable the AEP to evaluate education outcomes which would assist in the continuous quality improvement of the provision of audiology education.